Le 29ème Festival International de la Peinture de Cagnes-sur-Mer 1997. - Beguiristiain, Maria Teresa; Bot, Marc Le; Chambert, Christian; Constant, Roland; Gaudet, Michel; Gisbourne, Mark; Kelly, Liam; Lemaire, Gérard-Georges; Paakkola, Mikko; Reunders, Tineke; Sutton, Gertrud Kobke; Verlinden, Frédérique; et al. (Cagnes-sur-Mer: Festival International de la Peinture, 1997)
Mields, Rune ; Winner, Gerd ; Van den Bulcke, Guy ; Bekaert, Piet ; Fjederholt, Preben ; Olsen, John ; Lozano ; Lazkano ; Hytönen, Petri ; Kare, Antero ; Olivier, Pierre ; Goezu, André ; Grandville, Nathalie De la ; Kelly, Bernadette ; Madden, Anne ; Brocquy, Louis Le ; Egan, Felim ; Crone, David ; Plug, Marian ; Frieling, Gijs ; Kit, Cristina Mio U ; De Guimaraes, José ; Rielly, James ; English, Simon ; Fenger-Krog, Louise ; Malmeström, Tamara
biografie
Frans
boek